Effect of Ca2+ on microtubules and axoplasmic transport of sciatic nerve in vivo - GAN Si-de; FAN Ming-ming; HE Guo-ping (Acta Pharmacologica Sinica, 2016)
CaCl2, EGTA or colchicines were injected into rat sciatic nerve to observe their effects on centrifugal transport of [3H]leucine which was injected into L4,5 ventral horns 3 h earlier. The radioactivities of every 5-mm segment of ventral roots and the nerves were determined by scintillation and the nerves were examined under an electron microscope as well.CaCl2 25 mM or EGTA 5 mM decreased the transport distance of labeled protein mildly. CaCl2 50-200 mM or EGTA 10 mM or colchicines 100-200 mM induced a great decrease or even disappearance of microtubules and blocked the transport around the injected site. Sham microinjection into the nerve did not affect the microtubules and transport. By injection of CaCl2 25 mM or EGTA 5 mM combined with colchicines 50 mM, their effects on microtubules or transport were additive. The results indicated that maintenance of a certain level of axoplasmic Ca2+ concentration was necessary for the polymerization of microtubules and axoplasmic transport in vivo. Ca2+ played a regulatory role in axoplasmic transport through the depolymerization of microtubules, thus microtubules were involved in the mechanism of axoplasmic transport.